Using the geographic detector model to identify factors controlling the bioavailability of Sr isotopes in China - Zhang, Xueyan; Ma, Xin; Wang, Xueye (Frontiers in Earth Science, 2023)
Strontium isotope ratios (87Sr/86Sr) are a widely applied tool in provenance applications in archaeology, paleoecology, forensics, and food science. Bedrock Sr is naturally and anthropogenically transferred to other reservoirs on the Earth’s surface through interactions with the hydrosphere, atmosphere, and biosphere. We attempt to reassess the contribution of the spatial distribution of bioavailable strontium isotopes using the geographic detector model (GDM). Our study reveals that the watershed factor explains 50.35% of the spatial variation of bioavailable Sr isotopes, while the climate, terrain, geology, and soil explain 14.41%, 4.94%, 4.63%, and 4.70% of the spatial variation of bioavailable Sr isotopes. The factors influencing the spatial variation of bioavailable Sr isotopes in China were ranked as follows: basin > climate > terrain > geology > soil type. The nonlinear enhancements of the interactions between the watershed and geology explained 59.90% of the spatial variation in bioavailable Sr isotopes, indicating that natural processes still control the bioavailability of strontium isotopes in China. Based on the synthesized river-water isotopic data, the large-scale bioavailable Sr isoscape discussed herein can be useful for migratory studies in China. The enrichment of strontium isotope data to refine Sr isotopes, as well as the search for better data on possible controlling factors, will make the analysis more comprehensive and provide a solid foundation for explaining strontium isotope migration.